PEMANFAATAN ASAP CAIR (LIQUID SMOKE) DARI HASIL PEMBAKARAN KAYU MERBAU (Intsia bijuga) SEBAGAI MEDIA PUPUK CAIR - Errin Aldian (JURNAL TECHLINK, 2021)
This study aims to reduce organic waste that is still a problem today by making organic waste into liquid smoke as well as materials used using biomass from merbau wood so that it can be used as liquid fertilizer as well as organic pesticides. The parameters measured in this study were using C-Organic, Macro Nutrient (N,P,K), N-Organic and pH acidity levels produced by liquid smoke from merbau wood based on the decree of the Minister of Agriculture No. 261/KPTS/SR.310/M/4/2019. Based on the results of research liquid smoke from merbau wood produced within 5 hours has a different mass weight with a temperature ratio of 250oC and 450oC. The result of utilization of merbau wood waste into liquid smoke is the resulting content value has not been able to meet the standard quality standards that have been set.